Effect of Fertilization Package on Vegetative Growth of Tejakula Tangerine (Citrus reticulata cv. Tejakula) After Transplanting to the Field - Rai, I Nyoman; Wijana, Gede; Mintarajasa, Jaya Duarsa (Universitas Panji Sakti, 2025)
Farmers have applied fertilization but have not achieved optimal vegetative growth of Tejakula tangerine plants. This study aims to find a combination of fertilization packages that can provide the best response to vegetative growth and improve the soil quality of Tejakula tangerine plants after moving to the field. The research was conducted in Tembok Village, Tejakula District, Buleleng Regency, Bali from July to December 2023. The experiment used a one-factor Randomized Block Design (RBD) with fertilization package treatment consisting of 3 levels, namely: 5 kg cow manure per tree, 5 kg cow manure + mycorrhizal biofertilizer 20 spores/50 g volcanic sand carrier + probiotic liquid organic fertilizer 20% concentration per tree and 5 kg cow manure + urea 50 g + SP-36 25 g + KCl 20 g per tree. Each treatment was repeated 8 times, resulting in 24 experimental units. Observational data were analyzed using the Analysis of Variance (ANOVA) test, and further tests were carried out using the Least Significant Difference (LSD) test. The results showed that the fertilizer package treatment had a very significant effect on the variable number of primary branches and leaf P nutrient content, significantly affected the variable number of plant stem diameter and leaf chlorophyll content, but had no significant effect on the variable number of plant height, relative water content (RWC) of leaves and leaf color. The package of cow manure + inorganic fertilizer influenced the vegetative growth of Tejakula tangerine after transplanting to the field very significantly on the increase in primary branches, significantly influenced the increase in plant stem diameter and leaf chlorophyll content. The organic fertilization package + mycorrhizal biofertilizer + probiotic liquid organic fertilizer can improve the soil quality of Tejakula tangerine plants.